An Efficient Explicit Marching on in Time Solver for Magnetic Field Volume Integral Equation - Bin Sayed, Sadeed; Ulku, H. Arda; Bagci, Hakan (IEEE, 2015)
An efficient explicit marching on in time (MOT) scheme for solving the magnetic field volume integral equation is proposed. The MOT system is cast in the form of an ordinary differential equation and is integrated in time using a PE(CE)(m) multistep scheme. At each time step, a system with a Gram matrix is solved for the predicted/corrected field expansion coefficients. Depending on the type of spatial testing scheme Gram matrix is sparse or consists of blocks with only diagonal entries regardless of the time step size. Consequently, the resulting MOT scheme is more efficient than its implicit counterparts, which call for inversion of fuller matrix system at lower frequencies. Numerical results, which demonstrate the efficiency, accuracy, and stability of the proposed MOT scheme, are presented.
IEEE International Symposium on Antennas and Propagation / USNC/URSI National North American Radio Science Meeting -- JUL 19-24, 2015 -- Vancouver, CANADA